Implementasi Pendidikan Agama Kristen dalam Keluarga Plural (Studi Kasus Pada Keluarga Beda Agama) (Jurnal Pendidikan Agama dan Teologi, 2023)
The family is part of society and also the church. The family has various problems that often make the household collapse or not survive. One of the cases is families of different religions, various obstacles will definitely occur in it, especially in terms of celebrating ecclesiastical holidays, but what is experienced by the families in this study is different, families are able to place Christian Religious Education as the basis for building families with different beliefs. This study used a case study type research in which the subjects in this study were 1 family with different beliefs. This research was conducted with the aim of revealing various forms of implementation of Christian Religious Education in families of different religions. The results of this study indicate that the forms of implementation of Christian religious education in families of different religions are open communication, knowledge of the Christian religion, respect for differences, involvement in Christian religious activities, and giving examples of behavior. Form